Perbedaan Pengaruh Latihan Medicine Ball Throw dan Resistance Band terhadap Kemampuan Lemparan ke Dalam pada Permainan Sepakbola Atlet Putra Usia 11-12 Tahun SBB Asri Gemolong Tahun 2026 - Arifudin Setiawan; Muh.Ikhwan Iskandar; Rendra Agung Prabowo (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the impact of Medicine Ball Throw and Resistance Band training on the accuracy and distance of throw-ins among male athletes aged 11–12 at SSB Asri Gemolong in 2026. Furthermore, this study compares the two techniques to identify the more effective training method. Statistical findings summarized two crucial points of the research: First, the comparative test indicated a significant difference in effects between the medicine ball throw and resistance band interventions on the football throw-in performance of male athletes aged 11-12 years at SSB Asri Gemolong Sragen (t observed = 3.486 > t table = 2.145; α = 5%). Second, the medicine ball throw method proved to be more effective in improving throw-in ability compared to the resistance band. This superiority was indicated by the improvement rate of the medicine ball throw group, which reached 63.53%, whereas the resistance band group only recorded an increase of 29.99%.